Initiating Payment of Trafficking Restitution from a Victims Perspective - Rina Melati Sitompul; Andi Maysarah (Kanun Jurnal Ilmu Hukum, 2021)
The objective of this study was to offer policy concept ideas in fulfilling restitution for the victims in accordance with the required attainment of justice. Restitution related to the payment of costs charged to the person based on a court decision that has permanent legally enforceable for the costs suffered by the victim or heir. This study used a normative method using a statutory approach and a case approach. From the three court decisions and one trafficking case in the constabulary, the victim's comprehension of the legal handling experienced is sufficient to accommodate the victim's wishes in obtaining victim's rights. Conclusions are drawn through an inductive to deductive thought process. Of the three decisions reviewed, it proved that the application of restitution payments was not able to fulfill a sense of justice for the victim. In fact, in practice, the fulfillment of compensation payments is in the non-penal space, from the perspective of victim recognition, it is sufficient to accommodate their wishes and hopes for the fulfillment of the expected restitution rights. In order to provide legal certainty for victims of the fulfillment of restitution rights, a legal breakthrough is required. The diversion method as a confirmation of ensuring the payment of the victim's restitution right is an offer. The concept of diversion can be carried out with the limitation of the criteria for the impact experienced by the victim, and the legality of legality is determined through a court decision or decision, as legal achievement through restorative justice is able to restore conflicts from perpetrators and victims.